2019
DOI: 10.3390/app9194007
|View full text |Cite
|
Sign up to set email alerts
|

Surface Patterns for Drag Modification in Volleyballs

Abstract: Surface patterns on objects are important in aerodynamics. We show how surface patterns on volleyballs modify their aerodynamic performances. Conventional volleyballs with six panels show different aerodynamic characteristics along transverse and diagonal directions. Interestingly, isotropic surface patterning with hexagons or dimples enables us to achieve isotropic aerodynamics. This result gives insight into surface-mediated flight controls of projectiles through resisting fluid media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
5
0
2
Order By: Relevance
“…Subsequently, a volleyball with a raised hexagon-shaped design on the surface (V5M5000 by Molten) was introduced in 2008 and has been adopted as the official ball by the NCAA (National Collegiate Athletic Association) Volleyball tournament and the USA Volleyball. The aerodynamic characteristics of these balls, having significantly different shapes and surface textures from those of traditional volleyballs, have been studied previously using wind-tunnel experiments [1][2][3]. Moreover, wind-tunnel experiments and CFD tests on various sports balls have been performed in previous studies [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a volleyball with a raised hexagon-shaped design on the surface (V5M5000 by Molten) was introduced in 2008 and has been adopted as the official ball by the NCAA (National Collegiate Athletic Association) Volleyball tournament and the USA Volleyball. The aerodynamic characteristics of these balls, having significantly different shapes and surface textures from those of traditional volleyballs, have been studied previously using wind-tunnel experiments [1][2][3]. Moreover, wind-tunnel experiments and CFD tests on various sports balls have been performed in previous studies [4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini senada dengan (Jalilian, 2014) yang menyatakan pengembangan sarana olahraga didasari dari pemahaman yang tumbuh pada perkembangan ilmu fisika yang dapat menjelaskan fenomena bagaimana olahraga tersebut dimainkan. Beberapa peneltian tentang bola voli yang sudah dilakukan diantaranya oleh (Asai et al, 2010), (Hong et al, 2018), (Hong et al, 2019), (Fitria & Suminah, 2020), (Irwanto et al, 2021).…”
Section: Pendahuluanunclassified
“…Since each panel was measured only five times, it cannot be said to be a statistically sufficient amount, but it was found that there is a difference in the variability of each ball and panel. In the previous fluid force measurement using a wind tunnel [7,11], the magnitude of the force applied to the ball varied with time, and it was reported that some panels had large amplitudes while others had small amplitudes. The results of the present study, which show that the variation in the drop point varies from panel to panel, are consistent with the previous result, indicating that the blurring of the floater serve varies from panel surface to panel surface.…”
Section: Ejection Experimentsmentioning
confidence: 99%
“…The fluid force on the ball has been investigated in wind tunnel experiments [5,6], with a hitting robot [7], and computational calculations [8][9][10]. The drag coefficient applied to the ball is large at low velocities, and decreases drastically with the transition from laminar to turbulent flow as the speed of the ball increases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation